Influence of the volume of hot plastic deformation on the processes of nitriding and tribotechnical properties of structural steel 18ХГТ - Клімін, В.В. (Problems of Tribology, 2014)
In this article attention is called to a new method of bulk hot plastic deformation which is not only intensifying chemical-thermal processing and increases tribological properties but it is giving the abilities of bulk thermal-chemical treatment of machine components shafts, cogwheels etc. with wear compensation of worn parts for their working capacity renovation without additional components and materials using.